2016
DOI: 10.1016/j.ijscr.2016.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Cordylobia rodhaini infestation of the breast: Report of a case mimicking a breast abscess

Abstract: IntroductionMyiasis, parasitic infestation of the body by fly larvae, caused by the Cordylobia rodhaini is very rare with only fourteen cases published since 1970. We present a rare case of myiasis mimicking a breast abscess.Presentation of caseA 17-year-old female presented with a nodular ulcerative lesion in her left breast 14 days following a trip to Ghana. She had been initially unsuccessfully treated with the antibiotic flucloxacillin following a misdiagnosis of a breast abscess. Following application of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Myiasis is known for its erythematous papular lesions, which may turn into furuncles or pustules. They usually present a central orifice through which the larva breathes, and there may be serous, serosanguinolent or seropurulent secretion [ 2 , 5 , 8 , 9 ]. Additionally, it may produce pain, pruritus, burning, a sensation of movement and perilesional inflammatory reactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Myiasis is known for its erythematous papular lesions, which may turn into furuncles or pustules. They usually present a central orifice through which the larva breathes, and there may be serous, serosanguinolent or seropurulent secretion [ 2 , 5 , 8 , 9 ]. Additionally, it may produce pain, pruritus, burning, a sensation of movement and perilesional inflammatory reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it may produce pain, pruritus, burning, a sensation of movement and perilesional inflammatory reactions. Although systemic symptoms are rare, fever, adenopathies, asthenia, adynamia, agitation and insomnia may be present [ 2 , 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cordylobia rodhaini lesions are usually bigger and more painful, sometimes mimicking real abscesses, and can involve subcutaneous edema or lymphangitis . In a recent review of published cases, nine patients out of 26 reported were infected by five or more larvae.…”
Section: Discussionmentioning
confidence: 99%